2017
DOI: 10.1039/c7ra03752j
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin-3-gallate (EGCG) inhibits fibrillation, disaggregates amyloid fibrils of α-synuclein, and protects PC12 cells against α-synuclein-induced toxicity

Abstract: EGCG protects transduced PC12 cells against α-Syn-induced cytotoxicity by inhibiting the overexpression and fibrillation of α-Syn in the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 60 publications
3
33
0
Order By: Relevance
“…This finding agrees with a previous observation for κ-casein fibrils, which interact with high affinity with EGCG, but showed no indication of modification the structure or of redirection of the aggregation pathway (Hudson et al, 2009). However, various studies have reported the EGCG-induced remodelling of diverse amyloid fibrils and a formation of soluble amorphous aggregates at neutral pH (Bieschke et al, 2010;Palhano et al, 2013;Shoval et al, 2008;Ehrnhoefer et al, 2008;Zhao et al, 2017;Zhu et al, 2016;Chandrashekaran et al, 2011;He et al, 2009;Daniels et al, 2019). Our seeding data did not suggest a seeding efficiency change or dissociation of the pre-formed α-synuclein fibrils; EGCG interacts with the fibril surface and therefore changes the interaction with ThT, as well as being able to interfere with the seeding if present at sufficiently high concentrations.…”
Section: /22supporting
confidence: 91%
See 1 more Smart Citation
“…This finding agrees with a previous observation for κ-casein fibrils, which interact with high affinity with EGCG, but showed no indication of modification the structure or of redirection of the aggregation pathway (Hudson et al, 2009). However, various studies have reported the EGCG-induced remodelling of diverse amyloid fibrils and a formation of soluble amorphous aggregates at neutral pH (Bieschke et al, 2010;Palhano et al, 2013;Shoval et al, 2008;Ehrnhoefer et al, 2008;Zhao et al, 2017;Zhu et al, 2016;Chandrashekaran et al, 2011;He et al, 2009;Daniels et al, 2019). Our seeding data did not suggest a seeding efficiency change or dissociation of the pre-formed α-synuclein fibrils; EGCG interacts with the fibril surface and therefore changes the interaction with ThT, as well as being able to interfere with the seeding if present at sufficiently high concentrations.…”
Section: /22supporting
confidence: 91%
“…A well-studied polyphenol is Epigallocatechin-3-gallate (EGCG), the main polyphenol found in green tea. Biochemical studies indicate the neuroprotective action of EGCG, which has been suggested to effectively inhibit the aggregation of a number of amyloidogenic peptides and proteins, including α-synuclein (Bieschke et al, 2010;Zhao et al, 2017;Qing et al, 2016;Roy and Bhat, 2019;Teng et al, 2019), amyloid-β (related to AD) (Liu et al, 2015;Bieschke et al, 2010), islet amyloid polypeptide (related to type-II diabetes) (Lee et al, 2019;Xu et al, 2017), huntingtin exon 1 (related to Huntington's disease) (Ehrnhoefer et al, 2006), tau (related to AD and tauopathies) (Wobst et al, 2015), superoxide dismutase (related to amyotrophic lateral sclerosis) (Srinivasan and Rajasekaran, 2017), prion proteins (related to prion diseases) (Rambold et al, 2008;Roberts et al, 2009) and others. EGCG has the ability to prevent the formation of toxic prefibrillar oligomers as well as to inhibit amyloid fibril formation and has been proposed to remodel existing amyloid fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…A well-studied polyphenol is epigallocatechin-3-gallate (EGCG), the main polyphenol found in green tea. Biochemical studies indicate the neuroprotective action of EGCG, which has been suggested to inhibit the aggregation of a number of amyloidogenic peptides and proteins effectively, including α-synuclein [31][32][33][34][35], amyloid-β (related to AD) [31,36], islet amyloid polypeptide (related to type-II diabetes) [37,38], huntingtin exon 1 (related to Huntington's disease) [39], tau (related to AD and tauopathies) [40], superoxide dismutase (related to amyotrophic lateral sclerosis) [41], prion proteins (related to prion diseases) [42,43], and others. EGCG has the ability to prevent the formation of toxic prefibrillar oligomers, as well as to inhibit amyloid fibril formation and has been proposed to remodel existing amyloid fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…The desired outcome of such an interaction is to block the formation of toxic oligomeric species and to possibly dissociate preformed fibrillar aggregates into non-toxic species [31]. Epigallocatechin-3-gallate (EGCG), the main polyphenol found in green tea, has been reported to effectively inhibit the aggregation of a number of amyloidogenic peptides and proteins, including amyloid-β (related to AD) [32,33], α-synuclein (related to PD) [33][34][35][36], islet amyloid polypeptide (related to type-II diabetes) [37,38], huntingtin exon 1 (related to Huntington's disease) [39], tau (related to AD and tauopathies) [40], superoxide dismutase (related to amyotrophic lateral sclerosis) [41], prion proteins (related to prion diseases) [42], and others. In addition, it has been shown that EGCG can induce remodeling and/or dissociation of pre-existing aggregate species [33,34,36,43,44].…”
Section: Introductionmentioning
confidence: 99%